Carcinosarcoma of the stomach: A rare tumor for an unusual localization. Review of the literature - Marco, Federica Di; Piombino, Eliana; Portale, Teresa Rosanna; Magro, Gaetano; Pesce, Antonio (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Di Marco F, Piombino E, Portale TR, Magro G, Pesce A. Carcinosarcoma of the stomach: A rare tumor for an unusual localization. Review of the literature. Turk J Gastroenterol 2019; 30(12): 1066-9.